Robert B. Parker's Bull River [compact disc, unabridged] - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Cole and Hitch novel., 2014)
After hunting down murderer and bandito Captain Alejandro Vasquez, Territorial Marshal Virgil Cole and Deputy Everett Hitch return him to Citadel to stand trial.